2019
DOI: 10.1007/s10624-018-9535-4
|View full text |Cite
|
Sign up to set email alerts
|

Everyday barricades: bureaucracy and the affect of struggle in trade unions

Abstract: Employees in global workplaces commonly suggest they are being failed by trade union representatives that betray the political ideals of their institutions. The tenacity of this discourse requires interrogation, since the notion persists even in contexts that lack evidence of such practices occurring. Based upon a comparison of Kazakhstan and India, we suggest that there is a fundamental slippage between the emotive aspect of union politics and the banal realties of institutional processes. We explore how cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Inspired by Lazar (2017 andKeskula and, several of our papers use ethnography to explore unions as collective ethical-political projects, while unpacking the norms and cultures from which these projects emerge. For instance, Soul (this issue) scrutinizes the often naturalized concept of 'union membership'.…”
Section: Anthropologies Of Unionism and Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by Lazar (2017 andKeskula and, several of our papers use ethnography to explore unions as collective ethical-political projects, while unpacking the norms and cultures from which these projects emerge. For instance, Soul (this issue) scrutinizes the often naturalized concept of 'union membership'.…”
Section: Anthropologies Of Unionism and Labourmentioning
confidence: 99%
“…We detail the union activities that occur in the small, poorly-funded offices where local union staff tend to the daily needs of members and the incidents on the shop-floor that lead to workers describing their unions as corrupt or useless (c.f. Keskula and Sanchez 2019). Our ethnographies explore how these, often banal, activities shape how workers and community members understand unions' potential for political action and how they form their worker identities.…”
Section: Anthropologies Of Unionism and Labourmentioning
confidence: 99%
“…By this term, I refer to a range of processes and institutions that are valued by people because they can impact the world around them. Many of these technologies are collective and, under the right conditions, can include trade unions and political parties (Kesküla and Sanchez 2019). As broadly feminist research on factory employment has revealed, even in contexts of social marginalization employees may find their labor satisfying when it is regarded as part of a collective project of meaningful transformation (Lynch 2012;Ngai 2005;Plankey-Videla 2012;Wright 2006).…”
mentioning
confidence: 99%
“…Nash issued a critique of corporate hegemony (Nash 1989). She did not use these terms but she would have recognized the "kinning practices" of the union and also the corporation, and she would have considered unions to be an "ethical-political project" as contemporary scholars term them (McNamara and Spyridakis this issue, see Kesküla and Sanchez 2019;Lazar 2018).…”
mentioning
confidence: 99%